The method of investigation of basic project parameters of microsatellite by random search - V. N. Blinov; A. I. Lukyanchik; V. V. Shalay (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A significant number of the main design parameters of the small upper stage for the group launch of small spacecraft with a propulsion system with a displacement fuel supply system determines the relevance of the random search method. The aim of the work is to create a method of selecting the main design parameters of the small upper stage by random search. The mathematical model based on the dimensional-mass model of the calculated mass determination provides the choice of the optimal mass of the upper stage, taking into account the complex relationships of the studied parameters